Moderating effect of entrepreneurial self-efficacy on the strength of the mediated relationship between networking capabilities and SME performance via entrepreneurial competencies - Ali , Bishar Adan (International Journal of Economics, Business and Management Studies, 2024)
The purpose of this study was determine the effect of networking capabilities on firm performance while controlling for entrepreneurial competencies, to determined the moderating effect of entrepreneurial self-efficacy on the relationship between entrepreneurial competencies and SME performance and ultimatrely to establish the moderating effect of entrepreneurial self-efficacy on the strength of the mediated relationship between networking capabilities and Small and Mediam Enterprises (SME) performance via entrepreneurial competencies. The study sdopted the positivist research philosophy asserting the existence of an objective reality that can be quantified, offering both explanatory and predictive capabilities. The research adopted an explanatory research design. Hayes Model 4 and 59 process Macro approach was used to analyse data and test the hypotheses. The results showed that networking capabilities had a significant direct effect on firm performance. The study also revealed that the interaction of entrepreneurial self- efficacy between the entrepreneurial competencies and firm performance was significant. Ultimately, the study determined the conditional indirect effect of Entrepreneurial Self-Efficacy (ESE) on the strength of the mediated relationship between networking capabilities and SME performance via entrepreneurial competencies. The study concluded that positive and significant moderated mediation analysis was evident. More importantly, the conditional indirect effect was much stronger with firms having lower levels of ESE. The study concluded that entrepreneurial self-efficacy has significant conditional indirect effect on the strength of the mediated relationship between networking capabilities and SME performance via entrepreneurial competencies. These findings emphasise the importance of self-efficacy, networking capabilities and competencies of the entrepreneurs as a predictor to improved firm performance.